Caveolin3 Stabilizes McT1-Mediated Lactate/Proton Transport in Cardiomyocytes. Issue 6 (25th January 2021) - Peper, Jonas; Kownatzki-Danger, Daniel; Weninger, Gunnar; Seibertz, Fitzwilliam; Pronto, Julius Ryan D.; Sutanto, Henry; Pacheu-Grau, David; Hindmarsh, Robin; Brandenburg, Sören; Kohl, Tobias; Hasenfuss, Gerd; Gotthardt, Michael; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: CAV3 (caveolin3) variants associated with arrhythmogenic cardiomyopathy and muscular dystrophy can disrupt post-Golgi surface trafficking. As CAV1 (caveolin1) was recently identified in cardiomyocytes, we hypothesize that conserved isoform-specific protein/protein interactions orchestrate unique cardiomyocyte microdomain functions. To analyze the CAV1 versus CAV3 interactome, we employed unbiased live-cell proximity proteomic, isoform-specific affinity, and complexome profiling mass spectrometry techniques. We demonstrate the physiological relevance and loss-of-function mechanism of a novel CAV3 interactor in gene-edited human induced pluripotent stem cell cardiomyocytes. Objective: To identify differential CAV1 versus CAV3 protein interactions and to define the molecular basis of cardiac CAV3 loss-of-function. Methods and Results: Combining stable isotope labeling with proximity proteomics, we applied mass spectrometry to screen for putative CAV3 interactors in living cardiomyocytes. Isoform-specific affinity proteomic and co-immunoprecipitation experiments confirmed the monocarboxylate transporter McT1 (monocarboxylate transporter type 1) versus aquaporin1, respectively, as CAV3 or CAV1 specific interactors in cardiomyocytes. Superresolution stimulated emission depletion microscopy showed distinct CAV1 versus CAV3 cluster distributions in cardiomyocyte transverse tubules. CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/Cas9 nuclease)-mediated CAV3 knockout uncovered a stabilizing role for McT1 surface expression, proton-coupled lactate shuttling, increased late Na + currents, and early afterdepolarizations in human induced pluripotent stem cell-derived cardiomyocytes. Complexome profiling confirmed that McT1 and the Na, K-ATPase form labile protein assemblies with the multimeric CAV3 complex. Conclusions: Combining the strengths of proximity and affinity proteomics, we identified isoform-specific CAV1 versus CAV3 binding partners in cardiomyocytes. McT1 represents a novel class of metabolically relevant CAV3-specific interactors close to mitochondria in cardiomyocyte transverse tubules. CAV3 knockout uncovered a previously unknown role for functional stabilization of McT1 in the surface membrane of human cardiomyocytes. Strikingly, CAV3 deficient cardiomyocytes exhibit action potential prolongation and instability, reproducing human reentry arrhythmias in silico. Given that lactate is a major substrate for stress adaption both in the healthy and the diseased human heart, future studies of conserved McT1/CAV3 interactions may provide rationales to target this muscle-specific assembly function therapeutically.